Musical bands in the procession - Mumbai Archive Project Team (Jio Institute, 2024)
The organizing committees each have their own music band. These bands, playing saxophones, trumpets, drums, cymbals, and various other musical instruments, accompany the procession as it makes its way through Versova Koliwada.